2017
DOI: 10.5830/cvja-2017-025
|View full text |Cite
|
Sign up to set email alerts
|

The effect of iloprost and sildenafil, alone and in combination, on myocardial ischaemia and nitric oxide and irisin levels

Abstract: SummaryAimInsufficient oxygen supply to organs and tissues due to reduced arterial or venous blood flow results in ischaemia, during which, although ATP production stops, AMP and adenosine continue to be produced from ATP. The fate of irisin, which causes the production of heat instead of ATP during ischaemia, is unknown. Iloprost and sildenafil are two pharmaceutical agents that mediate the resumption of reperfusion (blood supply) via vasodilatation during ischaemic conditions. Our study aimed to explore the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 41 publications
0
7
0
1
Order By: Relevance
“…Spinal cord injury (SCI) is one of the devastating traumas in central nervous system diseases, which leads to paralysis, palsy and even death in severe cases ( Singh et al, 2014 ). Reports spanning various countries demonstrated that SCI has become a common disease affecting millions of individuals worldwide ( Noonan et al, 2012 ; Smith et al, 2010–2015 ; Saberi et al, 2016 ). Though great efforts have been made to seek effective treatment method for SCI ( Ma et al, 2020 ; Zheng et al, 2020 ), no optimal therapeutic strategy has been achieved yet.…”
Section: Introductionmentioning
confidence: 99%
“…Spinal cord injury (SCI) is one of the devastating traumas in central nervous system diseases, which leads to paralysis, palsy and even death in severe cases ( Singh et al, 2014 ). Reports spanning various countries demonstrated that SCI has become a common disease affecting millions of individuals worldwide ( Noonan et al, 2012 ; Smith et al, 2010–2015 ; Saberi et al, 2016 ). Though great efforts have been made to seek effective treatment method for SCI ( Ma et al, 2020 ; Zheng et al, 2020 ), no optimal therapeutic strategy has been achieved yet.…”
Section: Introductionmentioning
confidence: 99%
“…Intriguingly, a similar study conducted by Aydin et al on myocardial ischaemic rats implied both iloprost and sildenafil can reverse down-regulated irisin immunoreactivity in the hepatocytes of liver tissue (Ref. 84). These tissue ischaemia-eliminating effects to some extent accelerated the blood supply through vasodilatation, cellular reoxygenation and enhanced irisin synthesis.…”
Section: Various Liver Injury and Relevant Illnessmentioning
confidence: 85%
“…In central nervous system (CNS), irisin expression has been detected in the Purkinje cells of the cerebellum ( Dun et al, 2013 ), spinal cord and cerebral cortex ( Huh et al, 2012 ). In peripheral tissues, it is reported in liver, kidney ( Aydin, 2014 ), salivary glands ( Aydin et al, 2013 ), cardiac muscles ( Aydin et al, 2017 ), skin and testis ( Aydin et al, 2014 ). Among the male reproductive tissues, testis bears the highest irisin expressions followed by prostate gland, while within testis, irisin is mostly expressed in the developing germ cells, peritubular cells and Leydig cells ( The Human Protein Atlas, 2021 ; Figure 1 ).…”
Section: Irisin: An Adipo-myokine and Its Receptorsmentioning
confidence: 99%